Big Data Analytics Adoption And Its Impact On Organizational Performance In Malaysian Small Medium Enterprise - Goh, Hsiao Yee (2024)
Building on Technological, Organizational and Environmental (TOE) model, this study intends to investigate the influence of TOE factors has on BDA adoption decision and its impact on organizational performance. Furthermore, drawing from the perspective of the Resource-based View (RBV), this study asserts the importance of comprehending the impact of BDA on the decision-making process (DMP) to gain a deeper understanding of the link between BDA adoption and organizational performance. Finally, drawing on Balance Scorecard (BSC), this study incorporated non-financial measures such as customer satisfaction, internal business process efficiency, learning and growth with financial measures in assessing organizational performance.